1974
DOI: 10.3758/bf03203271
|View full text |Cite
|
Sign up to set email alerts
|

Perceived size and perceived distance in stereoscopic vision and an analysis of their causal relations

Abstract: Effects of visual angle and convergence upon the perceived sizes and perceived distances of a familiar object (playing card) and a nonrepresentational object (blank white card) were investigated by means of a projector stereoscope with polarizing filters. The results obtained with six Ss indicated that size estimates increased nearly proportionally as the visual angle increased and decreased nearly linearly as the convergence increased. Distance estimates decreased nearly linearly as either the visual angle or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
(30 reference statements)
2
28
1
Order By: Relevance
“…(1) as described in the introduction section if s is replaced by sЈ, i.e., the perceived size of the actual object instead of the afterimage. Some experiments (e.g., Foley, 1968;Oyama, 1974) have confirmed the hypothesis but other experiments (e.g., Gogel et al, 1963) have disconfirmed it. The confirmation or disconfirmation of the hypothesis depends on the instructions, the methods of measurements, full-cues or reduced cues to distance and depth, and so on.…”
mentioning
confidence: 58%
“…(1) as described in the introduction section if s is replaced by sЈ, i.e., the perceived size of the actual object instead of the afterimage. Some experiments (e.g., Foley, 1968;Oyama, 1974) have confirmed the hypothesis but other experiments (e.g., Gogel et al, 1963) have disconfirmed it. The confirmation or disconfirmation of the hypothesis depends on the instructions, the methods of measurements, full-cues or reduced cues to distance and depth, and so on.…”
mentioning
confidence: 58%
“…On the other hand, Oyama (1974), using visual angle and convergence as stimulus variables, found, except in the case of one of his six subjects, no relation between perceived size and perceived distance. Both were directly and independently determined by the stimulus variables.…”
Section: Discussionmentioning
confidence: 99%
“…A causal analysis of inference, developed by Blalock (1962) and Simon (1954), can be applied to determine which of these explanations is valid, when perceived depth and perceived size are simultaneously obtained under various combinations of stimulus cues. Oyama (1974) applied this type of analysis and found that perceived size and perceived distance were directly determined by visual angle and by convergence. The observed relation between perceived size and perceived distance was not based on a direct causal relation between them.…”
mentioning
confidence: 99%
“…In stereoscopic space, various studies have been conducted (e.g., Foley, 1966Foley, , 1968Foley, , 1970Howard & Rogers, 1995;Julesz, 1971;Oyama, 1974). For example, Foley (1966) found that the perceptual egocentric distance lay outside the Vieth-Muller circle (VMC).…”
Section: Palabras Clave: Percepción De La Profundidad Fotografía VImentioning
confidence: 99%